The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1097/00004650-199804000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and Chronic Fatigue: The Holistic Perspective

Abstract: Fibromyalgia syndrome (FMS) and chronic fatigue syndrome (CFS) are not new conditions, but they are receiving more attention as more research is conducted. These two conditions are primarily women's health problems. In some instances, there may be a genetic predisposition for these conditions. The impact of FMS and CFS can be devastating both physically and emotionally. The treatment plan must be interdisciplinary and holistic and include alternative therapies if the client and family are to be truly supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When the cause of a patient's problem is unknown, health-care professionals may question the patient's own story [8,9,12]. In this study, there were feelings of inferiority among the participants, when health care professionals indicated that they had inflicted their injury or illness on themselves.…”
Section: Experiences Of Care Situations When Dignity Was Not Fully Upmentioning
confidence: 81%
See 2 more Smart Citations
“…When the cause of a patient's problem is unknown, health-care professionals may question the patient's own story [8,9,12]. In this study, there were feelings of inferiority among the participants, when health care professionals indicated that they had inflicted their injury or illness on themselves.…”
Section: Experiences Of Care Situations When Dignity Was Not Fully Upmentioning
confidence: 81%
“…According to an earlier research [8][9][10][11][12], this questionnaire included a special requirement for, in narrative form, collecting experiences of care situations when dignity was not fully upheld.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation